2021
DOI: 10.2196/18591
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention Strategies for Community-Based Longitudinal Studies in Diverse Urban Neighborhoods

Abstract: Longitudinal, natural experiments provide an ideal evaluation approach to better understand the impact of built environment interventions on community health outcomes, particularly health disparities. As there are many participant engagement challenges inherent in the design of large-scale community-based studies, adaptive and iterative participant engagement strategies are critical. This paper shares practical lessons learned from the Physical Activity and Redesigned Community Spaces (PARCS) study, which is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These procedures are similar to other parental cessation trials which involved the assessment of the effects of the intervention on both the parent’s tobacco outcomes and child’s TSE outcomes [ 30 , 31 , 32 ]. Further, the present study included incentives and convenient home visits, as these may decrease study-related burdens [ 17 ]. Other reasons not assessed in this study, but that were reported as reasons why parents consented for their child to be enrolled in other pediatric studies included: parents’ interest in being more involved in their child’s clinical treatment; parents being approached by clinical or research staff whom they trusted or had a relationship with; and parents’ belief that participation would benefit their child [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures are similar to other parental cessation trials which involved the assessment of the effects of the intervention on both the parent’s tobacco outcomes and child’s TSE outcomes [ 30 , 31 , 32 ]. Further, the present study included incentives and convenient home visits, as these may decrease study-related burdens [ 17 ]. Other reasons not assessed in this study, but that were reported as reasons why parents consented for their child to be enrolled in other pediatric studies included: parents’ interest in being more involved in their child’s clinical treatment; parents being approached by clinical or research staff whom they trusted or had a relationship with; and parents’ belief that participation would benefit their child [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the recruitment of parental smokers into tobacco cessation interventions may potentially have a high impact, resulting in large decreases in adult tobacco use and reductions in pediatric tobacco smoke exposure (TSE)-related morbidity [ 5 , 14 , 15 , 16 ]. Despite the growing number of studies about barriers and limitations to participating in a RCT [ 9 , 17 , 18 , 19 , 20 , 21 ], there is a research gap in our understanding of the barriers in parents’ willingness to participate in a RCT in the PED or UC setting in which the parent and not the pediatric patient is the targeted research participant. This information is needed to maximize costly recruitment and enrollment efforts and to obtain the targeted study sample size needed to adequately assess study outcomes in RCTs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our community design team did not include any men, and men were underrepresented among our community participants more generally. Although a community-based participatory research approach to recruitment was successful, other best practices for recruitment, such as face-to-face interaction, were unable to be initiated due to the COVID-19 pandemic [ 27 - 29 ]. Future studies should use strategies that promote the recruitment of men, such as prioritization of men by the study team, including men as part of the recruitment team, and expanding community partners.…”
Section: Discussionmentioning
confidence: 99%
“…Our community design team did not include any men, and men were underrepresented among our community participants more generally. Although a community-based participatory research approach to recruitment was successful, other best practices for recruitment, such as face-to-face interaction, were unable to be initiated due to the COVID-19 pandemic [27][28][29]. Future studies should use strategies that promote the recruitment of men, such as prioritization of men by the study team, including men as part of the recruitment team, and expanding community partners.…”
Section: Discussionmentioning
confidence: 99%